Kata Tugas Bahasa Sunda dalam Karangan Laporan Peristiwa - Masitoh, Imas Siti; Nurjanah, Nunuy (UPI, 2019)
Interest in researching specific task words in the event report essay, is due to the large number of task words that do not have lexical meaning, but have a big influence when understanding the contents of the essay. The purpose of this study is to describe the form and type of assignment words. In this study, descriptive methods were used as well as test and documentation techniques which were analyzed using elemental analysis techniques directly in the essay report of class VIII-B students at SMP Negeri 12 Bandung. Based on the results of the study, four forms and four types of task words were found. Forms of task words found include (1) basic words (one syllable, two syllables, three syllables), (2) affixed words (front affixes, rear affixes, front-back affixes), (3) repetitive words ( dwimurni), and (4) compound words (KK + P, P + KT, P + KB, P + KSam, and KS + KBil). Then the types of assignment words found include (1) affirmative words (phatic categories, introduction, stages, determinants, aspect enhancers, and enhancers of modalities), (2) conjunctions (coordinative, subordinative, and inter sentence), (3) front soy sauce (meaning place, direction of destination, origin / beginning, tool, comparison, actor, limiter, purpose, accompaniment and object), and (4) interjection (meaning happy / happy). The lesson about assignment words is important for student of junior high school, because the assignment words functions as an explanation between the parts of the sentence in an essay. Therefore, students' essays will be easier to understand and quality because of the accuracy of the use of the word assignment.AbstrakKetertarikan meneliti khusus kata tugas dalam karangan laporan peristiwa, disebabkan oleh banyaknya kata tugas yang tidak memiliki makna leksikal, tapi besar pengaruhnya ketika memhami isi karangan. Tujuan penelitian ini untuk mendeskripsikan bentuk dan jenis kata tugas. Metode yang digunakan adalah metode deskriptif serta teknik tes dan dokumentasi yang dianalisis menggunakan teknik analisis unsur langsung pada karangan laporan peristiwa siswa kelas VIII-B SMP Negeri 12 Bandung. Berdasarkan hasil penelitian, ditemukan empat bentuk dan empat jenis kata tugas. Bentuk kata tugas yang ditemukan meliputi (1) kata dasar (satu suku kata, dua suku kata, tiga suku kata), (2) kata berimbuhan (awalan, akhiran, gabungan), (3) kata ulang (semu), dan (4) kata majemuk (KK + P, P + KT, P + KB, P + KSam, dan KS + KBil). Lalu jenis kata tugas yang ditemukan meliputi (1) adverbia (partikel penegas, pengantar, tahapan, penentu, penambah aspek, dan penambah modalitas), (2) kata sambung (koordinatif, subordinatif, dan antar kalimat), (3) preposisi (bermakna tempat, arah tujuan, asal/awal, alat, pembanding, pelaku, pembatas, tujuan, penyerta, dan objek), serta (4) kata seru (bermakna senang/gembira). Materi tentang kata tugas terbilang penting untuk siswa SMP, sebab kata tugas berfungsi sebagai penjelas antar bagian kalimat dalam sebuah karangan. Oleh sebab itu, karangan siswa akan lebih mudah dipahami dan berkualitas jika tepat dalam penggunaan kata tugas.